Investigating Problem Solving and Mathematical Connections in Solving the Fermi-Dirac Equation - Misbah, Misbah; Trisnowati, Eli; Rahim, Abd; Zb, Aminah (International Journal of Education and Teaching Zone, 2022)
This study aimed to describe the problem-solving abilities and mathematical connections of the sixth-semester students of Physics Tadris in the Statistical Physics course, especially the Bose-Einstein Equation Material. This type of research is quantitative descriptive research. Data collection in this study used a cognitive test technique in the form of a description test to measure students' mathematical abilities, which amounted to 8 questions, of which four were used to measure problem-solving abilities, and four were used to measure students' mathematical connections. Data analysis was carried out descriptively to determine the profile of students' mathematical abilities and the distribution of predicate achievement on the ability of problem fractions and students' mathematical connections. The results showed that students' average problem-solving ability and mathematical connection were in the Pretty Good category.